Developing Power-Law Fluid Flow in The Entrance Region of a Parallel Plate Channel - Rehman, Sadia (2024)
A Master of Science thesis in Chemical Engineering by Sadia Rehman entitled, “Developing Power-Law Fluid Flow in The Entrance Region of a Parallel Plate Channel”, submitted in March 2024. Thesis advisor is Dr. Rachid Chebbi. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).